Relationship between Emotional Intelligence and Gender Difference: An Empirical Study - Das, Rajendra Prasad; Sahu, Tapas Lata (Prabandhan: Indian Journal of Management, 2015)
Emotions differentiate human beings from animals. It is a subjective conscious experience characterized by psycho-physiological expressions, biological reactions, and mental status. The objective of the current study was to assess whether there existed any differences in emotional intelligence among post graduate students with respect to their gender. A standardized questionnaire was used to conduct the study and data was collected from 100 post graduate students using random sampling method. Emotional intelligence of the sample respondents was measured with the help of a scale developed by Hyde, Pethe, and Dhar (2002) consisting of 34 items. Data was analyzed using SPSS and the results indicated that the level of emotional intelligence among female students was higher than it was in male students.